Implementasi Asas Proporsionalitas dan Jaminan Kepastian Hukum dalam Tabungan Perumahan Rakyat - M. Daffa Rizky Ansor; Aditya Nugraha; Fayu Karmila; Ariyanto (CV Rewang Rencang, 2024)
The aim of the law is to create justice, certainty and benefit, the Public Housing Savings program is the government's effort to overcome the problem of housing inequality, however there is resistance from the public towards the Public Housing Savings program which is based on a lack of public trust in the Tapera program and the feeling that Tapera contributions are burdensome for workers. The aim of this research is to analyze and determine the implementation of the principle of proportionality and guarantee of legal certainty for Public Housing Savings participants. The method used in this research is empirical juridical, with a Sociology of Law, Legislation and Conceptual approach. Data collection through interviews, questionnaires and literature study. The research results show that the Tapera program is not in accordance with the principle of Proportionality, because Tapera participants with middle to upper incomes do not receive benefits other than savings and fertilizer proceeds that can be taken when membership ends which are not commensurate with their contributions, and participants with low incomes feel that the 2.5% contribution is burdensome because there is a burden on other income. Article 39 letter d of the Tapera Law seems to obscure BP Tapera's responsibility to be held accountable in court for the negligence of third parties appointed by BP Tapera, and data shows that the Tapera program has low community legitimacy and thus requires a guarantee.